BAŞLANGYÇ SYNPLARDA OKATMAGYŇ ADATY, IŞJEŇ, INTERAKTIW USULLARY (Konferensiyalar | Conferences, 2024)
This article talks about the interactive method of teaching in the modern teaching practice, especially the types that help students to understand the new information they receive, think actively, and master the knowledge.